Correlation between Prodigiocin , Biofilm formation and Drug Resistant in Virulent Serratia marcescens. - Ali, Mun,im R; Alsakini, Ali H; Karim, Sawsan M (Al-Nahrain Journal of Science, 2013)
One hundred and fifty samples were collected from urine and blood, with a male to female ratio 1.45:1, culture positivity seen in the urinary tract infection was the most frequent (77%), followed by blood infection (18%). A total of 86 (57.33%) bacterial isolates were obtained. The study focused on 9 clinical isolates of Serratia marcescens (15.2%), differentiated into Prodigiosin producer (11.6%) and non- Prodigiosin producer (3.6%). Almost all isolates (6/9) showed visible growth at 37°C. All S. marcescens strains of different sources were hemolytic, whereas the formation of a pellicle was noticed among 7 isolates (77.77%) from 9 isolates. The biofilm formation performed was assessed through the crystal violet assay noticed that out of the 9 S. marcescens isolates 5 (55.5%) were non-adherent, 4 (44.4%) were weakly adherent, No isolate showed strongly adherent. The tube method for assay biofilm formation showed good correlation with the Tissue culture plate (TCP) method assay for biofilm forming isolates and total 2 (22.2%) isolate were picked up as strong and 5 (55.5%) were moderat biofilm producers. The tube test correlates well with the TCP test for biofilm producing isolates but it was difficult to discriminate between weak and biofilm negative isolates due to the variability in observed results by different observers. All 9 isolates were sensitive to the IPM and AZM (100%). The biofilm MICs were found to be much higher than the planktonic MICs. The medium with antibiotic used not inhibited the prodigiosin production at the MIC for planktonic cells. Therefore prodigiosin production in media with antibiotics used not marker of the growth and activity of bacterial cells. Biofilms are considerably less susceptible to antibiotics than their planktonic counterparts; biofilm production may vary largely among different strains of the same species isolated from different sites.